Toward balanced growth : quantity with quality : report of the National goals research staff (Washington : National Goals Research, 1970)
This report is designed not as a listing of specific goals to be sought, but as a springboard for discussion and aid to decision. It does not presume to say what our choices should be. Rather, it defines the questions, analyzes the debates and examines the alternative sets of consequences.
Includes bibliographical references
hza 29/01/2019
Loans
Keywords: Growth (social development); United States